Preparation method and application of caragana microphylla seed extract corrosion inhibitor
By using the illegal seeds to extract the corrosion agent of property preparation, the problem of severe corrosion of zinc electrode in zinc and air batteries and low battery capacity have been solved. The advantage of low cost.
Patent Information
- Application Number
- CN202411949044.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are problems in existing zinc-air batteries with severe corrosion of zinc electrodes and low battery capacity, and traditional electrolyte corrosion inhibitors have problems of environmental toxicity or high cost.
Use lemon seed extracts as a corrosion agent. By mixing the lemon seed powder with deodorized water, the rotary evaporates is used to steam and steam it, and is frozen and dry to prepare a corrosion agent for zinc and air batteries.
Effectively suppress the self -corrosion of zinc anode, reduce the rate of hydrogen analysis, improve the stability of the electrolyte and the discharge performance of zinc air batteries, and has the advantages of environmental protection and low cost.
Smart Images

Figure CN119372653A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc-air batteries, and in particular to a preparation method and application of a caragana seed extract corrosion inhibitor. Background Art
[0002] Zinc-air batteries have become a hot research topic for future energy storage and electric vehicle applications due to their high energy density, environmental friendliness and low cost. However, zinc-air batteries still face many challenges in practical applications, especially in terms of electrolyte stability and battery capacity. Zinc electrodes are prone to form zinc dendrites during charging and discharging, resulting in short circuits and low battery capacity; at the same time, in the alkaline environment of the electrolyte, zinc electrode corrosion and side reactions also hinder the improvement of battery performance. In order to address these problems, researchers have gradually turned their attention to the development and optimization of electrolyte corrosion inhibitors. As an effective means of regulation, electrolyte corrosion inhibitors can improve the performance of zinc-air batteries to a certain extent. They can inhibit the formation of zinc dendrites, slow down the corrosion of zinc electrodes, and increase the capacity of batteries. At present, common electrolyte corrosion inhibitors include organic small molecules, inorganic salts, and surfactants. By introducing suitable corrosion inhibitors into the electrolyte, not only can the deposition process of the zinc electrode be optimized, but also the overall performance of the battery can be improved and the battery capacity can be increased.
[0003] Traditional electrolyte corrosion inhibitors are mostly small organic molecules or inorganic compounds. Although they can improve battery performance to a certain extent, they often have problems such as environmental toxicity or high cost. Plant extracts, as a natural green corrosion inhibitor, have the advantages of abundant resources, low cost, and good degradability, and thus become a new direction for the research of electrolyte corrosion inhibitors. Polyphenol compounds, saponins, flavonoids, etc. in certain plant extracts have excellent antioxidant, film-forming and corrosion inhibition capabilities, which can effectively improve the behavior of zinc electrodes during charging and discharging, inhibit the growth of zinc dendrites, and reduce the occurrence of side reactions. At the same time, the introduction of plant extracts is expected to reduce the impact on the environment and promote the greening and sustainable development of zinc-air battery technology. Therefore, the application research of plant extracts as electrolyte corrosion inhibitors not only broadens the technical path of energy storage batteries, but also provides important ideas for the development of new electrolytes. Summary of the invention
[0004] Based on this, the present invention provides a preparation method and application of a caragana seed extract corrosion inhibitor, which solves the problems of high toxicity, environmental pollution, high cost and complex synthesis of existing corrosion inhibitors, as well as the problem of severe anode corrosion of zinc-air batteries under existing conditions and technologies, resulting in low battery capacity.
[0005] In order to solve the above technical problems, one of the objects of the present invention is to provide a method for preparing a corrosion inhibitor of Caragana seed extract, comprising the following steps: S1: After screening the caragana seeds, wash them with deionized water, dry them, and grind them into caragana seed powder using a grinder; S2: adding the Caragana seed powder prepared in S1 to deionized water, boiling and rotary evaporating using a rotary evaporator to obtain a crude Caragana seed extract, and vacuum filtering to remove the residue to obtain a mixture of Caragana seed extract and water; S3: The mixture of the Caragana seed extract and water obtained in S2 is placed in a refrigerator for freezing, and then vacuum freeze-dried to obtain a corrosion inhibitor for zinc-air batteries.
[0006] Preferably, the particle size of the caragana seed powder in S1 is 200 mesh.
[0007] Preferably, the drying temperature in S1 is 60-100° C., and the drying time is 36-60 h.
[0008] Preferably, the mass ratio of the caragana seed powder to the deionized water in S2 is 1:30-50.
[0009] Preferably, the rotary evaporation time of the rotary evaporator in S2 is 2-4 hours.
[0010] Preferably, the mixture of Caragana seed extract and water in S3 is placed in a refrigerator for 6-10 hours, and the vacuum freeze-drying temperature is -70°C to -90°C for 24-48 hours.
[0011] Based on the same inventive concept, the present invention also provides a high-efficiency zinc-air battery electrolyte, which is prepared from the following raw materials in parts by weight: 0.01-0.05 parts of corrosion inhibitor, 24 parts of strong alkali, and 95-105 parts of deionized water.
[0012] Preferably, the strong base is sodium hydroxide.
[0013] The above one or more technical solutions of the present invention have the following technical effects: 1) The present invention uses caragana seed extract as a corrosion inhibitor, which broadens the electrochemical stability window of the electrolyte and improves the stability of the electrolyte; 2) In the present invention, as the concentration of the corrosion inhibitor caragana seed extract increases, the corrosion rate gradually decreases; 3) In the present invention, as the concentration of the corrosion inhibitor caragana seed extract increases, the polarization resistance increases; 4) When the electrolyte corrosion inhibitor prepared by the present invention is used on the surface of zinc anode, it can effectively inhibit the self-corrosion of zinc anode, while reducing the hydrogen evolution rate and improving the corrosion inhibition efficiency; 5) When the electrolyte prepared by the invention is used in zinc-air batteries, it can effectively improve the discharge performance of zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0015] Figure 1 , Preparation process of electrolyte corrosion inhibitor for zinc-air battery; Figure 2 , open circuit curves of three-electrode systems assembled from Examples 4-8 and Comparative Example 1; Figure 3 , Nyquist plots of three-electrode systems assembled from Examples 4-8 and Comparative Example 1; Figure 4 , polarization curves of three-electrode systems assembled from Examples 4-8 and Comparative Example 1; Figure 5 , hydrogen evolution rate and hydrogen evolution inhibition efficiency diagram of Examples 4-8 and Comparative Example 1; Figure 6 , step discharge curves of zinc-air batteries assembled from Example 7 and Comparative Example 1; Figure 7 , constant current discharge curve diagram of the zinc-air battery assembled from Example 7 and Comparative Example 1; Figure 8 , SEM image of zinc metal after 1 h of exposure; Fig. 9 , SEM image of metallic zinc immersed in the solution prepared in Comparative Example 1 for 1 h; Fig.10 , SEM image of metallic zinc after immersing in the solution prepared in Example 7 for 1 h. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0017] Throughout the specification, unless otherwise specified, the terms used herein should be understood as having the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. If there is a conflict, the present specification takes precedence. The preparation process of the electrolyte prepared by the present invention is as follows Figure 1 shown.
[0018] Example 1 A method for preparing a corrosion inhibitor of Caragana korshinskii seed extract comprises the following steps: S1: Wash the caragana seeds with deionized water, pick out the impurities, dry them at 60°C for 60 h, and grind them into 200-mesh caragana seed powder using a grinder; S2: 50 g of the prepared Caragana seed powder was added to 1500 ml of deionized water and mixed, and the mixture was boiled and evaporated for 2 h using a rotary evaporator to obtain a crude Caragana seed extract, and the residue was removed by vacuum filtration to obtain a mixture of Caragana seed extract and water; S3: The mixture of Caragana seed extract and water was placed in a refrigerator for 6 h, and then vacuum freeze-dried at -70°C for 48 h to obtain a corrosion inhibitor for zinc-air batteries.
[0019] Example 2 A method for preparing a corrosion inhibitor of Caragana seed extract comprises the following steps: S1: Wash the caragana seeds with deionized water, pick out the impurities, dry them at 100°C for 36 h, and grind them into 200-mesh caragana seed powder using a grinder; S2: 50 g of the prepared Caragana seed powder was added to 2500 ml of deionized water, and the mixture was boiled and evaporated using a rotary evaporator for 4 h to obtain a crude Caragana seed extract, and the residue was removed by vacuum filtration to obtain a mixture of Caragana seed extract and water; S3: The mixture of Caragana seed extract and water was placed in a refrigerator and frozen for 10 h, and then vacuum freeze-dried at -90°C for 24 h to obtain a corrosion inhibitor for zinc-air batteries.
[0020] Example 3 A method for preparing a corrosion inhibitor of Caragana seed extract comprises the following steps: S1: Clean the caragana seeds with deionized water, remove the impurities, dry them at 80°C for 48h, and grind them into 200-mesh caragana seed powder using a grinder; S2: 50 g of the prepared Caragana seed powder was added to 2000 ml of deionized water and mixed, and the mixture was boiled and evaporated using a rotary evaporator for 3 h to obtain a crude Caragana seed extract, and the residue was removed by vacuum filtration to obtain a mixture of Caragana seed extract and water; S3: The mixture of Caragana seed extract and water was placed in a refrigerator for 8 h, and then vacuum freeze-dried at -80°C for 36 h to obtain a corrosion inhibitor for zinc-air batteries.
[0021] Example 4 Weigh 24 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.01 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 ml volumetric flask to obtain a corrosion inhibitor concentration of 100 mg·L -1 High-efficiency zinc-air battery electrolyte.
[0022] Example 5 Weigh 24 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.02 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 ml volumetric flask to obtain a corrosion inhibitor concentration of 200 mg·L -1 High-efficiency zinc-air battery electrolyte.
[0023] Example 6 Weigh 24 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.03 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 ml volumetric flask to obtain a corrosion inhibitor concentration of 300 mg·L -1 High-efficiency zinc-air battery electrolyte.
[0024] Example 7 Weigh 24 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.04 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 ml volumetric flask to obtain a corrosion inhibitor concentration of 400 mg·L -1 High-efficiency zinc-air battery electrolyte.
[0025] Example 8 Weigh 24 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.05 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 ml volumetric flask to obtain a corrosion inhibitor concentration of 500 mg·L -1 High-efficiency zinc-air battery electrolyte.
[0026] Comparative Example 1 Weigh 24 g of NaOH, dissolve it in deionized water, cool to room temperature, and dilute it to a 100 ml volumetric flask to obtain 100 ml of 6 M sodium hydroxide solution.
[0027] In order to further verify the effect of the electrolyte prepared in the present invention on the self-corrosion performance and discharge performance of the zinc anode, test examples 1-4 were respectively subjected to electrochemical tests, hydrogen evolution tests, discharge performance tests, and related tests such as the corrosion degree of metal zinc.
[0028] Test Example 1 Electrochemical test: The electrochemical method was carried out on a CHI760E electrochemical workstation using a traditional three-electrode system. The working electrode (WE) was a circular zinc anode with an exposed area of 0.785 cm², the auxiliary electrode (CE) was a platinum electrode, and the reference electrode (RE) was a Hg / HgO electrode immersed in a Luggin capillary filled with 1 mol / L NaOH solution. The zinc anode was polished with 400#, 800#, 1500#, and 2000# sandpaper until the surface was smooth, degreased with anhydrous ethanol, then rinsed with deionized water and dried, immersed in the electrolyte, and the change in open circuit potential (OCP) within 1000 seconds was recorded. After that, the electrochemical impedance spectroscopy (EIS) test was performed according to the open circuit potential to observe the effect of the corrosion inhibitor on the internal resistance of the solution. The test frequency range was 10m Hz to 100k Hz, the test amplitude was 5 mV, and the impedance data obtained were analyzed using ZSimpWin software and an equivalent circuit model. Subsequently, potentiodynamic polarization (PDP) tests were performed at a scan rate of 1 mV·s⁻¹ within the potential range of ±250 mV of the open circuit potential. The corrosion current density of the zinc electrode in the electrolyte was fitted by the Tafel curve, and the effect of the corrosion inhibitor in the electrolyte on the corrosion behavior of the zinc electrode could be observed.
[0029] The electrolytes prepared in Examples 4-8 and Comparative Example 1 were subjected to open circuit potential tests to observe the change of potential over time. The test duration was 1000 seconds in total. Figure 2 As shown in the figure, as the test time progresses, the open circuit potential gradually shifts negatively at the beginning, indicating that more zinc participates in the reaction, and the curve gradually becomes smooth at the end, indicating that the corrosion rate of zinc in the solution remains basically unchanged. Compared with the blank solution, the value of the open circuit potential decreases significantly after adding different concentrations of corrosion inhibitor, and reaches the minimum when the solubility of the corrosion inhibitor is 400 mg / L, indicating that the hydrogen evolution corrosion of the zinc anode is suppressed. Preliminary analysis shows that this may be due to the fact that the corrosion inhibitor molecules are adsorbed on the surface of the zinc anode to form a protective film, which prevents the sodium hydroxide solution from directly contacting the zinc anode.
[0030] like Figure 3 As shown in the figure, with the addition of the corrosion inhibitor, the anodic part of the polarization curve moves to the lower current density area, and the corrosion potential also shifts positively, while the cathode curve does not change basically, which indicates that the corrosion inhibitor is an anodic corrosion inhibitor. In addition, the corrosion potential and corrosion current density decrease at the same time, indicating that the polar functional groups in the corrosion inhibitor molecules are adsorbed on the zinc surface to form a layer of complexes, thereby blocking the active sites of hydrogen evolution corrosion.
[0031] The corrosion potential was calculated using the Tafel extrapolation method ( E corr )、Corrosion current density( I corr ) and other polarization parameters, corrosion inhibition efficiency ( ) is obtained by the following formula:
[0032] Among them, I corr represents the corrosion current density of the zinc anode in Comparative Example 1, and I corr(inh) The corrosion current density of the zinc anode in Examples 4-8 is shown in Table 1: Table 1 Polarization parameters of zinc anodes in electrolytes prepared in Examples 4-8 and Comparative Example 1
[0033] As shown in Table 1, with the addition of corrosion inhibitor, the corrosion potential of zinc anode gradually shifted positively and the corrosion current density decreased, indicating that the corrosion inhibitor played an inhibitory role in the corrosion of zinc anode. When the concentration of corrosion inhibitor reached 400 mg / L, the corrosion current density (I corr ) from 0.6 mA·cm -2 Down to 0.13 mA·cm -2 The maximum corrosion inhibition efficiency reaches 78.33%.
[0034] like Figure 4 As shown in the figure, all Nyquist curves have a similar shape, consisting of a flattened semicircle and a straight line, indicating that the corrosion of the zinc anode is controlled by two processes, which is controlled by the charge transfer process at the interface between the electrode and the solution in the high-frequency region and by the concentration diffusion step in the low-frequency region. The diameter of the semicircle gradually increases with the increase of the concentration of the corrosion inhibitor, indicating that the corrosion inhibitor gradually adsorbs on the surface of the zinc metal to form a film, which increases the charge transfer resistance at the interface. The capacitive reactance arc in the Nyquist diagram is not an ideal semicircle, which is due to the dispersion effect caused by the uneven distribution of the electrode surface. After adding the corrosion inhibitor, the shape of the Nyquist curve did not change, indicating that the corrosion mechanism did not change due to the addition of the corrosion inhibitor.
[0035] The impedance data is obtained by fitting the equivalent circuit diagram, where R s Represents the liquid junction resistance, C dl is the double layer capacitance, R ct represents the charge transfer resistance, Z w Represents diffusion resistance. Corrosion inhibition efficiency The calculation formula is as follows:
[0036] Where R ct,inh , R ct,0 Represents the charge transfer resistance value of the solution containing the corrosion inhibitor and the blank solution, in Ω·cm 2The fitted impedance parameters and calculated corrosion inhibition efficiency are shown in Table 2: Table 2 EIS fitting data of electrolytes prepared in Examples 4-8 and Comparative Example 1
[0037] It can be seen from the table that as the concentration of corrosion inhibitor increases, the charge transfer resistance R ct When the concentration of zinc anode increases, the corrosion inhibition efficiency increases. When the added concentration is 400 mg / L, the maximum corrosion inhibition efficiency reaches 80.47%. When the concentration continues to increase, the charge transfer resistance and corrosion inhibition efficiency decrease, which may be because the extract molecules compete for adsorption on the zinc anode surface, resulting in a decrease in adsorption amount.
[0038] Test Example 2 In order to study the self-corrosion phenomenon of zinc, a hydrogen evolution experiment was conducted by collecting hydrogen in a well-sealed EP tube. The zinc rod was cut into round blocks with a radius and thickness of 1 cm, and placed in solutions without and with different concentrations of corrosion inhibitors. The outlet of the EP tube was blocked with a well-sealed rubber stopper, and a medical syringe with a range of 10 ml was inserted inverted into the rubber stopper to collect the precipitated hydrogen. The test lasted for a total of 10 days. After 10 days, the volume of the piston in the syringe moved up was the volume of the precipitated hydrogen. The hydrogen evolution rate ( ) and corrosion inhibition efficiency ( ) is calculated using the following formula:
[0039]
[0040] in, represents the volume of hydrogen evolution (ml), A is the exposure area of zinc anode in the electrolyte (cm²), and T represents the exposure time (day). and They represent the hydrogen evolution rate of zinc anode in solutions without corrosion inhibitor and with corrosion inhibitor, respectively.
[0041] like Figure 5 As shown in the figure: when the concentration of the corrosion inhibitor reaches 400 mg / L, the hydrogen evolution rate increases from 0.54 ml•cm -2 •d -1 Reduced to 0.18 ml•cm -2 •d -1 The maximum corrosion inhibition efficiency reached 67%. This is basically consistent with the results obtained from the electrochemical test, indicating that the corrosion inhibitor has a significant inhibitory effect on the corrosion of the zinc anode.
[0042] Test Example 3 (1) Speed performance test: The speed performance test of a battery refers to a method for testing the discharge performance of a battery at different current densities. The speed performance test of the zinc-air battery in this paper was carried out on the Wuhan Blue Electric multi-channel system, and the current densities were set to 1, 2, 5, 10 and 1 mA cm -2 Each stage of the test lasts 10 minutes. Figure 6 As shown, it can be seen from the step discharge curve that the voltage value of the battery with the addition of the corrosion inhibitor is significantly higher than that of the comparative example 1, indicating that the addition of the corrosion inhibitor inhibits the corrosion of the zinc anode and allows more zinc to participate in the battery reaction.
[0043] (2) Constant current discharge test: The constant current discharge test means that the system discharges the battery at a constant current to test the relationship between the discharge voltage and the discharge time. After the constant current discharge of the battery is completed, the mass of the consumed zinc sheet is standardized, and then the specific capacity or energy density of the battery can be calculated. The current density is set to 10 mA cm -2 .like Figure 7 As shown, at a discharge current density of 10 mA·cm -2 When the discharge time is 1 hour, the addition of corrosion inhibitor increases the specific capacity from 282.51 mAh·g -1 Increased to 476.23 mAh g -1 , indicating that the battery can release more energy after adding corrosion inhibitor when consuming the same mass of zinc anode, which is consistent with the result obtained by the step discharge curve.
[0044] Test Example 4 The polished zinc sheet was immersed in the solutions prepared in Comparative Example 1 and Example 7 at 25°C for 12 h. Afterwards, the samples were washed with deionized water and anhydrous ethanol, and the surface morphology was studied using a scanning electron microscope (SEM). Figure 8 As shown in Figure 1, the surface of the zinc anode polished with sandpaper is obviously smooth and flat. Fig. 9 As shown in the figure, after immersion in the solution prepared in Comparative Example 1 for 12 hours, the zinc surface became rough, the white layer on the surface was ZnO, and obvious corrosion pits appeared, indicating that local corrosion occurred on the zinc anode surface. Fig.10 As shown in the figure, after immersing in the solution prepared in Example 7 for 12 hours, it was observed that the surface of the zinc anode had fewer corrosion marks and the surface became smooth. This shows that the introduction of the corrosion inhibitor inhibited the serious corrosion of the zinc anode. This is because the corrosion inhibitor molecules are adsorbed on the surface of the zinc anode to form a thin film, which prevents the zinc anode from reacting with OH - direct contact.
Claims
1. A method for preparing a corrosion inhibitor of Caragana korshinskii seed extract, characterized in that: The steps include: S1: After screening the caragana seeds, wash them with deionized water, dry them, and grind them into caragana seed powder using a grinder; S2: adding the Caragana seed powder prepared in S1 to deionized water, boiling and rotary evaporating using a rotary evaporator to obtain a crude Caragana seed extract, and vacuum filtering to remove the residue to obtain a mixture of Caragana seed extract and water; S3: The mixture of the Caragana seed extract and water obtained in S2 is placed in a refrigerator for freezing, and then vacuum freeze-dried to obtain a corrosion inhibitor for zinc-air batteries.
2. The method for preparing the corrosion inhibitor of Caragana korshinskii seed extract according to claim 1, characterized in that: The particle size of the Caragana seed powder in S1 is 200 mesh.
3. The method for preparing the corrosion inhibitor of Caragana korshinskii seed extract according to claim 1, characterized in that: The drying temperature in S1 is 60-100°C, and the drying time is 36-60 h.
4. The method for preparing the corrosion inhibitor of Caragana korshinskii seed extract according to claim 1, characterized in that: The mass ratio of the caragana seed powder to the deionized water in S2 is 1:30-50.
5. The method for preparing the corrosion inhibitor of Caragana korshinskii seed extract according to claim 1, characterized in that: The rotary evaporation time of the rotary evaporator in S2 is 2-4 h.
6. The method for preparing the corrosion inhibitor of Caragana korshinskii seed extract according to claim 1, characterized in that: The mixture of the Caragana seed extract and water in S3 is placed in a refrigerator for 6-10 hours, and the vacuum freeze drying temperature is -70°C to -90°C, and the time is 24-48 hours.
7. An application of a corrosion inhibitor prepared by the method according to any one of claims 1 to 6, characterized in that: The corrosion inhibitor is used for high-efficiency zinc-air battery electrolyte, and the electrolyte is prepared from the following raw materials in parts by weight: 0.01-0.05 parts of corrosion inhibitor, 24 parts of strong alkali, and 95-105 parts of deionized water.
8. The use of the corrosion inhibitor according to claim 7, characterized in that: The strong base is sodium hydroxide.
Citation Information
Patent Citations
Preparation method of zinc electrode used for zinc-air battery
CN102509774A
Electrolyte corrosion inhibitor, electrolyte for aluminum air cell and aluminum air cell
CN105140595A
Plant extract copper corrosion inhibitor and preparation method thereof
CN113930771A
Environment-friendly reinforced concrete corrosion inhibitor as well as preparation method and application thereof
CN114988745A
Ionic soil resist and preparation method and application thereof
CN115058253A